Rancang Bangun Aplikasi Training Needs Analysis Berdasarkan Kompetensi Pada PT. Tunggal Djaja Indah - Huda, Maghvirul; Sulistiowati, Sulistiowati; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT. Tunggal Djaja Indah (PT. TDI) is a leading paint manufacturer in Indonesia. ISO 9001 which has obtained by PT. TDI is a proof of the seriousness of the company. Current training process in PT. TDI is using a form that called a skill map. The assessment of training needs using skill map is force the head of department to fill the competency by themselves. It makes the result of the training needs is not align to meet company’s standard.To solve this problem, we need a solution that can identify training needs that are categorized by knowledge, skill, and attitude based on companys’ standard. The way to solve it is make a training needs analysis (TNA) application based on competency.Based on the results of the training needs analysis application, the application can help stakeholders to identify training needs based on the competencies that are categorized by the level of knowledge, skill, and attitude. so it can help to reduce the gap between the competence of employees with competencies expected by the company.